Appropriating innovations: entangled knowledge in Eurasia, 5000-1500 BCE - Maran, Joseph; Stockhammer, Philipp (Oxbow Books, 2017)
Innovation minus modernity : revisiting some relations of technical and social change / Cornelius Schubert -- From counting to writing : the innovative potential of bookkeeping in Uruk period Mesopotamia / Kristina Sauer -- Uruk, pastoralism and secondary products : was it a revolution? a view from the Anatolian highlands / Maria Bianca D'Anna and Giulio Palumbi -- The "green revolution" in prehistory : late Neolithic agricultural innovations as a technological system / Maria Ivanova -- The spread of productive and technological innovations in Europe and Near East : an integrated zooarchaeological perspective on secondary animal products and bronze utilitarian metallurgy / Haskel J. Greenfield -- Early wagons in Eurasia : disentangling an enigmatic innovation / Stefan Burmeister -- Contextualising innovation : cattle owners and wagon drivers in the North Caucasus and beyond / Sabine Reinhold, Julia Gresky, Natalia Berezina, Anatoly R. Kantorovich, Corina Knipper, Vladimir E. Maslov, Vladimira G. Petrenko, Kurt W. Alt and Andrey B. Belinsky -- Innovation, interaction and society in Europe in the 4th millennium BCE : the "traction complex" as innovation and "technology cluster" / Maleen Leppek -- Wheels of change : the polysemous nature of early wheeled vehicles in 3rd millennium BCE central and northwest European societies / Joseph Maran -- Appropriating draught cattle technology in southern Scandinavia : roles, context and consequences / Niels N. Johannsen -- Key techniques in the production of metals in the 6th and 5th millennia : prerequisites, preconditions and consequences / Svend Hansen -- The diffusion of know-how within spheres of interaction : modelling prehistoric innovation processes between South-West Asia and Central Europe in the 5th and 4th millennia BC / Florian Klimscha -- A comparative angle on metallurgical innovations in South-Western Asia : what came first? / Barbara Helwing -- The role of metallurgy in different types of early hierarchical society in Mesopotamia and Eastern Anatolia / Marcella Frangipane -- The use of bronze objects in the 3rd millennium BC : a survey between Atlantic and Indus / Lorenz Rahmstorf -- Appropriation of tin-bronze technology : a regional study of the history of metallurgy in early Bronze Age southern Mesopotamia / Ulrike Wischnewski -- Gonur Depe (Turkmenistan) and its role in the middle Asian interaction sphere / Federica Lume Pereira -- The appropriation of early bronze technology in China / Jianjun Mei, Yongbin Yu, Kunlong Chen, Lu Wang -- Patterns of transformation from the final Neolithic to the early Bronze age : a case study from the Lech Valley south of Augsburg / Ken Massy, Corina Knipper, Alissa Mittnik, Steffen Kraus, Ernst Pernicka, Fabian Wittenborn, Johannes Krause, Philipp W. Stockhammer -- Yet another revolution? weapon technology and use wear in late Neolithic and early Bronze age southern Scandinavia / Christian Horn
Keywords: Aufsatzsammlung; Vor- und Frühgeschichte; Landwirtschaft; Metallurgie; Rad; Gesellschaft; Technische Innovation; Technischer Fortschritt; Eurasien